Solar fresh heat-lock container / Nurhazimah Nordin ... [et al.] - Nordin, Nurhazimah; Mohd Nazir, Nur Sulaiman; Azmi, Mohamad Fakhruddin; Shahrul Layali, Arissa Elfeera; Selasa, Nur Izzati; Rahim, Nurul Izzati (2023)
The Solar Fresh Heat-Lock Container is the name of the innovation that is currently being discussed in this New Product Development (NPD). Specifically, this lunchbox product is powered by solar energy and incorporates various intelligent features. A solar system that is used to reheat food is combined with a gas detector (MQ-135) that serves as a sensor that will assist in detecting stale food in this innovation. The primary function of the solar system is to reheat food. In this report, additional explanations are provided regarding the applications of each component, as well as their functions, design, and implementation of technology. This new product development that is currently being discussed is a significant improvement upon existing items because it includes additional features to an existing product. Specifically, it enhances a product lunchbox that the Mr.DIY and Buffalo brands market. The main objective of this product is to create an invention that simplifies the process of obtaining hot meals for customers wherever they are. The product is designed to cater to a wide range of people who might find it helpful. This includes students, employees, housewives, tourists, and athletes who are involved in physical activities. This idea was conceived as a result of observing the difficulties that many people encounter when attempting to keep their meals warm while they are outside and how hard it is to make hot food that can be eaten anywhere.